Prediction of rowing functional threshold power using body mass, blood lactate and GxT peak power data. - Mc Grath, E.; Donne, B.; Mahony, B.; Fleming, N. (International Journal of Exercise Science, 2023)
Functional Threshold Power (FTP) is a validated index of a maximal quasi steady-state cycling intensity. The central component of the FTP test is a maximal 20-min time-trial effort. A model to predict FTP from a cycling graded exercise test (m-FTP) was published that estimated FTP without the requirement of the exhaustive 20-min time-trial. The predictive model (m-FTP) was trained (developed to find the best combination of weights and bias) on a homogenous group of highly-trained cyclists and triathletes. This investigation appraised the external validity of the m-FTP model vis-à-vis the alternate modality of rowing. The reported m-FTP equation purports to be sensitive to both changing levels of fitness, and exercise capacity. To assess this claim, eighteen (7 female, 11 male) heterogeneously-conditioned rowers were recruited from regional rowing clubs. The first rowing test was a 3-min graded incremental test with a 1-min break between increments. The second test was a rowing adapted FTP test. There were no significant differences between rowing FTP (r-FTP) and m-FTP (230 ± 64 versus 233 ± 60 W, respectively, F = 1.13, P = 0.80). Computed Bland-Altman 95% LoA between r-FTP and m-FTP were (-18 W to + 15 W), sy.x was 7 W, and 95 %CI of regression were 0.97 to 0.99. The r-FTP equation was demonstrated to be effective in predicting a rowers 20-min maximum power; further appraisal of the physiological response to rowing for 60-min at the corresponding calculated FTP requires investigation.